Study of Serum Ferritin and Glycemic Status in Type II Diabetic Patients (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: Diabetes mellitus has often found to be associated with iron dysregulation, manifested by increased serum ferritin level. Iron is essential for beta- cell insulin secretion, although, increasing concentration of iron and ferritin induce oxidative damage and dysfunction of pancreatic beta cells, leading to resistance to insulin, thus, consequent in hyperglycemia. Objective: To observe the association between serum ferritin and HbA1c concentration among type 2 DM patients. Methods: With an observational study design, the present study has been done among 63 purposively selected type 2 diabetic patients who attended the selected pathology institute during the period of January to June, 2021. Following availing the ethical approval from concerning ethical review committee and informed written consent of the patients, data regarding age, sex, height, weight, body mass index (BMI), diabetic duration, HbA1c concentration and serum ferritin level has been collected and recorded in a semi-structured questionnaire. Data were analyzed using Statistical Package for Social Science (SPSS) 20.Results: The study recorded that, the mean serum ferritin level was significantly higher among the poor glycemic control group than the good glycemic control group of respondents (p0.05).Conclusion: Higher serum ferritin level among diabetic patients with poor glycemic control may indicate that there is a pathological role of serum ferritin to induce changes in glycemic status, which requires further in depth studies to apprehend about the mechanism.JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 07-10